2014
DOI: 10.1073/pnas.1323025111
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR-Cas system enhances envelope integrity mediating antibiotic resistance and inflammasome evasion

Abstract: Significance Increasing the integrity of the bacterial envelope is necessary to allow the successful survival of bacterial pathogens within the host and allow them to counteract damage caused by membrane-targeting antibiotics. We demonstrate that components of a clustered, regularly interspaced, short palindromic repeats–CRISPR associated (CRISPR-Cas) system, a prokaryotic defense against viruses and foreign nucleic acid, act to regulate the permeability of the bacterial envelope, ultimately providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…Because the cas2 mutants exhibit their defect in the absence of added phage, plasmid, or nucleic acid and because L. pneumophila mutants lacking cas9, cas1, cas4, or the CRISPR array are not impaired (15), the infection event mediated by L. pneumophila Cas2 must be distinct from the functions that have been traditionally ascribed to Cas proteins and CRISPR-Cas systems. There are now a variety of studies demonstrating that there are roles for other Cas proteins that are unrelated to phage/plasmid immunity (21,(25)(26)(27)(28)(29); e.g., Cas9 of Francisella novicida promotes virulence in a murine model of disease (30), and Campylobacter jejuni Cas9 enhances invasion of epithelial cells (31).…”
mentioning
confidence: 99%
“…Because the cas2 mutants exhibit their defect in the absence of added phage, plasmid, or nucleic acid and because L. pneumophila mutants lacking cas9, cas1, cas4, or the CRISPR array are not impaired (15), the infection event mediated by L. pneumophila Cas2 must be distinct from the functions that have been traditionally ascribed to Cas proteins and CRISPR-Cas systems. There are now a variety of studies demonstrating that there are roles for other Cas proteins that are unrelated to phage/plasmid immunity (21,(25)(26)(27)(28)(29); e.g., Cas9 of Francisella novicida promotes virulence in a murine model of disease (30), and Campylobacter jejuni Cas9 enhances invasion of epithelial cells (31).…”
mentioning
confidence: 99%
“…In our hands, the LOF mutant displayed defects in predation but did not display altered motility or sporulation. It has been reported that CRISPR systems can regulate alternative functions, such as biofilm formation and swarming in Pseudomonas aeruginosa, EPS production in M. xanthus, and lipoprotein production in Francisella novicida (56,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…At 2 h postinfection, the bacteria were removed, and fresh medium containing 25 g of gentamicin/ml was added to the infected cells. At 16 h postinfection, the infected J774 macrophages were stained as described previously (28). Briefly, infected macrophages were permeabilized for 15 min in PBS containing 0.1% saponin and 3% bovine serum albumin (permeabilization buffer).…”
Section: Methodsmentioning
confidence: 99%